Främmande arters spridning med fartygsskrov som vektor - En kartläggning av trafikmönster till Göteborgs hamn - Johansson, Sara; Trost Lindblad, Matilda (My University, 2015)
The spread of alien species in marine environments is today classified as a major threat to biodiversity as invasive species can outcompete native species or spread diseases. Many of the invasive species has been disseminated with ship as vectors, mainly as biofouling on hulls or via ballast water. Vessels’ speed, operational pattern and type of antifouling are all important factors. Even if a hull looks clean there is a risk that some individuals are still being transported, leading to introduction and establishment of these species in a new environment, possibly causing problems. Risk assessments related to matching salinity and temperature in ports can constitute a basis for assessment of an alien species' potential of introduction in a new marine environment. Vessel statistics from the Port of Gothenburg's has been used in the main body of this report. These statistics have been used to analyze the flow of arriving vessels to the Port of Gothenburg and to map the largest ports, seen to the number of port calls to Gothenburg. The analysis of the port statistics showed that the five ports with most calls to Gothenburg were Fredrikshamn, Zeebrugge, Kiel, Rotterdam and Immingham. Almost all of these ports represented, with respect to temperature and salinity, medium to high risk of introduction of alien species in Gothenburg. Even the seven largest countries* with most calls to the port of Gothenburg are all in regions with similar temperatures. The conclusion of this report is that there is need of an assessment tool to be able to make decisions regarding if hull cleaning should be allowed or not in the port of Gothenburg. This assessment should be used to reduce the risk of spread of alien species via ships' hulls. It is suggested that each vessel application should be processed individually and partly be based on their trading patterns and previously visited ports. Less consideration should be given to the service speed, since all vessels are likely to introduce species to Gothenburg.
Keywords: Transportteknik och logistik; Hållbar utveckling; Transport; Transport Systems and Logistics; Sustainable Development; Transport